Computer-mediated communication and interpersonal communication in social media Twitter among adolescents - Novianto Yudha Laksana; Ahda Fadhilah (Journal of Social Studies (JSS), 2021)
Computer-Mediated Communication (CMC) becomes a new form of communication. Interpersonal communication has now moved into cyberspace thanks to CMC's role. CMC's implementation in touch is when two or more communion can only exchange information through computer media or the latest communication technology. CMC is categorized as synchronous if the connection delivers in a discussion room or chat room. In comparison, asynchronous CMC occurs when the communication process coincides. Twitter is one of the social media often used as a place of interaction on the internet. Based on Twitter data, 83% of Indonesian millennial users consider Twitter a reliable source for product information. This study aims to gain communication technology's meaning in giving birth to interpersonal relationships between Twitter users among adolescents. The research method uses online literature and observation studies. The results revealed that interactions on social media Twitter among adolescents could form intimate relationships among communication participants.